Desintegración familiar y su incidencia en el rendimiento académico de los alumnos de educación básica media de la Unidad Educativa San Carlos de la parroquia San Carlos del cantón Quevedo - Ríos Molina, Verónica Elizabeth (2018)
The present project investigates the family disintegration and its incidence in the Academic Performance of the students of average basic education of the Educational Unit "San Carlos". Family disintegration is the process that occurs when a couple makes the decision to separate, either by mutual agreement, or unilaterally due to the problems that arise. The project intends to carry out a study following up in a thorough manner and determine the degree to which the student is affected by the problems of the home, in this way it is planned to apply methodological skills that help the student to concentrate on their studies without being affected by their familiar surroundings. The research proposal seeks to improve this problem in middle school students and have had problems in the academic field due to the problems they have in their environment. The application of this research is only the beginning of programs or workshops that can be offered to educational actors as a strategy to support the homes of our environment to obtain meaningful learning